Immanent Externalities: The Reproduction of Life in Capital: di Rebecca Carson - Colombo, Alessandro (Quaderni Materialisti, 2024)
Recensione a R. Carson, Immanent Externalities: The Reproduction of Life in Capital, Brill, Leiden 2023, 212 pp. e Haymarket, Chicago 2024, 202 pp.